Hybrid trait speciation and Heliconius butterflies (2008)
Homoploid hybrid speciation (HHS) is the establishment of a novel species through introgressive hybridization without a change in chromosome number. We discuss different routes by which this might occur and propose a novel term, ‘hybrid trait speciation’, which combines the idea that hybridization can generate adaptive novelty with the ‘magic trait’ model of ecological speciation. Heliconius butterflies contain many putative examples of hybrid colour patterns, but only recently has the HHS hypothesis been tested explicitly in this group. Molecular data has shown evidence for gene flow between many distinct species. Furthermore, the colour pattern of Heliconius heurippa can be recreated in laboratory crosses between Heliconius melpomene and Heliconius cydno and, crucially, plays a role in assortative mating between the three species. Nonetheless, although the genome of H. heurippa shows evidence for hybridization, it is not a mosaic of the two parental species. Instead, ongoing hybridization has likely blurred any signal of the original speciation event. We argue that where hybridization leads to novel adaptive traits that also cause reproductive isolation, it is likely to trigger speciation.